ADIPOQ/adiponectin induces cytotoxic autophagy in breast cancer cells through STK11/LKB1-mediated activation of the AMPK-ULK1 axis. Issue 8 (3rd August 2017) - Chung, Seung J.; Nagaraju, Ganji Purnachandra; Nagalingam, Arumugam; Muniraj, Nethaji; Kuppusamy, Panjamurthy; Walker, Alyssa; Woo, Juhyung; Győrffy, Balázs; Gabrielson, Ed; Saxena, Neeraj K.; Sharma, Dipali
ABSTRACT: ADIPOQ/adiponectin, an adipocytokine secreted by adipocytes in the breast tumor microenvironment, negatively regulates cancer cell growth hence increased levels of ADIPOQ/adiponectin are associated with decreased breast cancer growth. However, its mechanisms of action remain largely elusive. We report that ADIPOQ/adiponectin induces a robust accumulation of autophagosomes, increases MAP1LC3B-II/LC3B-II and decreases SQSTM1/p62 in breast cancer cells. ADIPOQ/adiponectin-treated cells and xenografts exhibit increased expression of autophagy-related proteins. LysoTracker Red-staining and tandem-mCherry-GFP-LC3B assay show that fusion of autophagosomes and lysosomes is augmented upon ADIPOQ/adiponectin treatment. ADIPOQ/adiponectin significantly inhibits breast cancer growth and induces apoptosis both in vitro and in vivo, and these events are preceded by macroautophagy/autophagy, which is integral for ADIPOQ/adiponectin-mediated cell death. Accordingly, blunting autophagosome formation, blocking autophagosome-lysosome fusion or genetic-knockout of BECN1/Beclin1 and ATG7 effectively impedes ADIPOQ/adiponectin induced growth-inhibition and apoptosis-induction. Mechanistic studies show that ADIPOQ/adiponectin reduces intracellular ATP levels and increases PRKAA1 phosphorylation leading to ULK1 activation. AMPK-inhibition abrogates ADIPOQ/adiponectin-induced ULK1-activation, LC3B-turnover and SQSTM1/p62-degradation while AMPK-activation potentiates ADIPOQ/adiponectin's effects. Further, ADIPOQ/adiponectin-mediated AMPK-activation and autophagy-induction are regulated by upstream master-kinase STK11/LKB1, which is a key node in antitumor function of ADIPOQ/adiponectin as STK11/LKB1 -knockout abrogates ADIPOQ/adiponectin-mediated inhibition of breast tumorigenesis and molecular analyses of tumors corroborate in vitro mechanistic findings. ADIPOQ/adiponectin increases the efficacy of chemotherapeutic agents. Notably, high expression of ADIPOQ receptor ADIPOR2, ADIPOQ /adiponectin and BECN1 significantly correlates with increased overall survival in chemotherapy-treated breast cancer patients. Collectively, these data uncover that ADIPOQ/adiponectin induces autophagic cell death in breast cancer and provide in vitro and in vivo evidence for the integral role of STK11/LKB1-AMPK-ULK1 axis in ADIPOQ/adiponectin-mediated cytotoxic autophagy.